Numerical Investigation on the Collision between a Solitary Wave and a Moving Cylinder - Eren, Emir Taha; Malazi, Mahdi Tabatabaei; Temir, Galip (MDPI, 2020)
A 2-D numerical wave tank (NWT) was applied for solving the interaction between a solitary wave and a moving circular cylinder. The cylinder was placed at various positions from the tank bed floor. The cylinder can move at a constant horizontal velocity towards the solitary wave. The collision between a solitary wave and a moving cylinder is investigated at various conditions. A total of fifteen cases were studied. Ten different numerical simulations were used, including five submergence depths and two different moving velocities. The other five different numerical simulations were studied when the cylinder was unmoved in the NWT for comparing wave-structure interaction results between the moving and unmoved cylinders. The numerical results were obtained by calculating Reynolds-Averaged Navier-Stokes (RANS) equations and the volume of fluid (VOF) equations. Two different codes (User-Define-Function-UDF) were used for the generation of a solitary wave by moving a wave paddle and traveling cylinder in the NWT. The dynamic mesh method was applied for recreating mesh. First, the ability of CFD codes to generate a solitary wave by using wave paddle movement and the hydrodynamic forces of a moving cylinder were validated by numerical results. Further, the free-surface elevation and hydrodynamic forces were considered at various conditions. The numerical results show that moving cylinder velocity and the space between the cylinder and the tank bed floor have significant effects on surface displacement and hydrodynamic forces.
Keywords: wave-structure interaction; solitary wave; hydrodynamic forces; computational fluid dynamics (CFD); SIMULATION; FORCES; COMPUTATIONS; PROPAGATION; MODEL; Environmental Sciences & Ecology; Water Resources